The System of Governance in Malaysia, and the Extent of its Effectiveness in Islamic Banks and their Windows in Algeria: نظام الحوكمة في ماليزيا، ومدى فاعليتها في البنوك الإسلامية ونوافذها بالجزائر - Chourana, Mohamed; Bensayah, Sana; Kashi , Aghilas (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
هدفت هذه الدراسة إلى التعرف بصفة أساسية على مبادئ الحوكمة في المصارف الإسلامية وقياس مدى تطبيق تلك المبادئ في المصارف الإسلامية بالجزائر، لأنّ ما يميز الصيرفة الإسلامية هو وجود هيئة رقابية شرعية تنظر في الأنشطة والعقود التي تنتج عنها، وهذا ما يجعلها رائدة في عالم المال، لاتخاذ الشريعة الإسلامية مرجعا لها في كل البنود. ولذلك فإن بعض الدول وعلى رأسهم ماليزيا قامت بانشاء المجلس الإستشاري الشرعي على مستوى البنك المركزي الماليزي، وهو بمثابة السلطة المخولة بالتحقق من تطبيق أحكام الشريعة الإسلامية والإلزام بها في أعمال المصارف الإسلامية، وهو ما يمثل بالحوكمة الشرعية للمصارف الإسلامية. ويعمل هذا البحث على دراسة مدى توفير الإدارة السياسية على البنية التحتية اللاّزمة لتطوير الصناعة المالية الإسلامية في الجزائر الناشئة في كل أبعادها القانونية والشرعية والمالية، وهل يمكن إقامة نظام حوكمة شرعية بضوابطها ومعاييرها في إدارة المصارف الإسلامية بالجزائر، وإنشاء قانون مركزي للمجالس الاستشارية والشرعية؟ وما مدى اعتبار نظام الحوكمة ومدى فعاليته في المصارف الإسلامية، بالاستفادة من التجربة الماليزية؟ خصوصا وأن البنوك الإسلامية الجزائرية لا تحظى بثقة المجتمع المدني بسبب غياب أسس الحوكمة الشرعية بها الكلمات المفتاحية: حوكمة شرعية، المالية الإسلامية، الجزائر، ماليزيا Abstract This study aimed mainly at identifying the principles of governance in Islamic banks and measuring the extent to which these principles are applied in Islamic banks in Algeria, because what distinguishes Islamic banking is the existence of a Sharia supervisory board that looks at the activities and contracts that result from it. Islamic law as a reference for it in all items. Some countries, on top of them Malaysia, have established the Sharia advisory board at the level of the Central Bank of Malaysia, which is the authority empowered to verify the implementation of the provisions of Islamic law and its obligation in the work of Islamic banks Which represents the Sharia governance of Islamic banks. This research studies the extent to which the political administration provides the necessary infrastructure for the development of the emerging Islamic financial industry in Algeria in all fields, legal, sharia and Financial. Is it possible to establish a Sharia governance system with its controls and standards in the management of Islamic banks in Algeria, and to establish a central law for advisory and Sharia councils? And to what extent is the governance system considered and the extent of its effectiveness considered in Islamic banks, taking advantage of the Malaysian experience? Especially since Algerian Islamic banks do not have the confidence of civil society due to the absence of legitimate governance foundations in them. Keywords: Islamic governance, Islamic finance, Algeria, Malaysia